THE USE OF OUTRIGGER AND BELT TRUSS SYSTEM FOR HIGH-RISE CONCRETE BUILDINGS - Po Seng Kian (Institute of Research and Community Outreach - Petra Christian University, 2001)
The outrigger and belt truss system is commonly used as one of the structural system to effectively control the excessive drift due to lateral load, so that, during small or medium lateral load due to either wind or earthquake load, the risk of structural and non-structural damage can be minimized. For high-rise buildings, particularly in seismic active zone or wind load dominant, this system can be chosen as an appropriate structure. This paper studies the use of outrigger and belt truss system for high-rise concrete building subjected to wind or earthquake load. Eight 40storey two dimensional models of outrigger and belt truss system are subjected to wind load; and five 60storey three dimensional models are subjected to earthquake load, analyzed and compared to find the lateral displacement reduction related to the outrigger and belt system location. For the two dimensional 40storey model, 65% maximum displacement reduction can be achieved by providing first outrigger at the top and second outrigger at the middle of the structure height. For the three dimensional 60storey structural model subjected to the earthquake load, about 18 % reduction in maximum displacement can be achieved with optimum location of the outrigger truss placed at the top and the 33rd level.